2018
DOI: 10.4038/gmj.v23i2.7975
|View full text |Cite
|
Sign up to set email alerts
|

Domestic violence exposure of married women in a rural area in Sri Lanka

Abstract: Introduction: Domestic violence (DV) is common but underreported in the world. In Sri Lanka, information with this regard is scarce. The present study investigated the domestic violence exposure of married women in a rural area in the country. Methods: Community based cross-sectional study was conducted among 400 women in a conveniently selected Public Health Midwife area in Isurumuniya, in Anuradhapura. A self-reported questionnaire measured lifetime experiences of physical, emotional and sexual violence with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…These findings are similar to a study in Iran, Sri Lanka, India. [ 18 19 26 ] This study also offered that IPV affects the timing of ANC utilisation, and there is no significant association found with the number of ANC visits by pregnant women. Same was reported by the researchers in Nepal that pregnant women exposed to IPV are less likely to register for ANC services.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…These findings are similar to a study in Iran, Sri Lanka, India. [ 18 19 26 ] This study also offered that IPV affects the timing of ANC utilisation, and there is no significant association found with the number of ANC visits by pregnant women. Same was reported by the researchers in Nepal that pregnant women exposed to IPV are less likely to register for ANC services.…”
Section: Discussionmentioning
confidence: 79%
“…[ 15 16 ] In this study, about 58% women ≥35 years of age have experienced IPV whereas the prevalence rate in Brazil was 45.2%, 54.5% in Iran, 49% in Sri Lanka and 43.4% in Portugal. [ 17 18 19 20 ] The number of ANC visits is associated with place of residence. The women from urban areas are more using ANC services than women from rural areas, which is in line with another research conducted in Ethiopia.…”
Section: Discussionmentioning
confidence: 99%
“…25% of children are reported as having witnessed violence at home (1). In Sri Lanka, the prevalence of domestic violence is high as 49% (2) and therefore the values could be higher. Catani and the group revealed that 97% of children in Northern part of the country have exposure to domestic violence (3).…”
Section: Domestic Violence Exposure and Depression Symptoms Among Ado...mentioning
confidence: 99%